Geographic information system techniques for the mapping of access routes, habitat suitability and variations in the distributions of common carp (Cyprinus carpio) throughout Malheur National Wildlife Refuge - Miller, Jordan (My University, 2012)
Geographic Information System Common carp (Cyprinus carpio) present a threat to biodiversity throughout the world. They have the potential to create a monoculture by out-competing the endemic species. Habitat degradation through turbation and resuspention of sediment through feeding processes creates a transition from a macrophyte-dominated clear water state to a phytoplankton-dominated turbid water state. Within the Harney Basin in southeast Oregon lies Malheur National Wildlife Refuge. It is composed of about 187,000 acres of diverse habitat, mostly falling under the wetland classification. This northern cold desert, characterized by low precipitation and the wetlands in the region are subject to feast-famine water regime, receiving around nine inches of precipitation annually. Malheur National Wildlife Refuge is a cornerstone in the Pacific Flyway for transitional habitat as well as breeding habitat for many species of waterfowl and colonial nesting birds. It is Oregon's most important waterfowl production area. Common carp pose a very significant threat to the integrity of the waterfowl and nesting bird habitat. The first carp were reported around 1950 and now out compete the native species for food and habitat. There have been constant effort to mitigate the issue of carp in Malheur's waters but the myriad of waterways and desirable feeding and spawning habitat and the relatively durable common carp make it an ongoing battle for effective management. One problem is the lack of data on carp distributions and habitat use. The advancements in geographic information systems and an abundance of spatial data creates an opportunity to apply ecological, habitat, and infrastructure data to the carp deterrence process. In this study, an application of the Habitat Suitability Model will be used to identify the most desirable habitat for carp in two stages of the year: high water and low water. By combining the available data, it is possible to identify acreages of suitable habitat for common carp during the high water season and with an updated dataset of the water delivery system, suitable areas for the common carp during the low water season can be identified. In this study, acreages of suitable spawning habitat for carp are identified as well as areas, which are inhabited by carp, and areas that are not. Five pilot areas are identified where carp barriers are being used to identify the possibility of a carp-free water delivery system. These models are to be utilized in the ongoing effort to minimize the common carp distributions, numbers and impacts on waterfowl habitat to the greatest extent possible.
Thesis (M.S.)--University of Wisconsin-River Falls, 2012. vi + 50 leaves. Includes bibliographical references (leaves 46-50).
Keywords: Oregon; Malheur National Wildlife Refuge; Carp--Control--Geographic information systems; Environmental aspects